2000
DOI: 10.1108/09578230010373598
|View full text |Cite
|
Sign up to set email alerts
|

The influence of school architecture on academic achievement

Abstract: Limited, dated information is available to school administrators concerning the influence that the built learning environment has on academic achievement. Given the population increases, volatile standardized test scores, demand for new schools, and deplorable conditions of school facilities in the United States, it is timely to investigate this neglected aspect of educational research. In the face of radical technological changes and curriculum innovations, much of the new public school architectural design i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
87
0
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(95 citation statements)
references
References 7 publications
0
87
0
3
Order By: Relevance
“…A few studies of the physical environment and student outcomes have been conducted (Earthman & Lemasters, 1998;Lemasters, 1997;Tanner, 2000Tanner, , 2006Wohlwill & vanVliet, 1985;Yarborough, 2001). With sporadic and often inconclusive information existing in the literature concerning the effects that the physical environment has upon students, there exists a need for current, valid, and reliable data to support or refute the perspectives underlying this inquiry.…”
Section: Tanner Defining the Physical Environmentmentioning
confidence: 99%
“…A few studies of the physical environment and student outcomes have been conducted (Earthman & Lemasters, 1998;Lemasters, 1997;Tanner, 2000Tanner, , 2006Wohlwill & vanVliet, 1985;Yarborough, 2001). With sporadic and often inconclusive information existing in the literature concerning the effects that the physical environment has upon students, there exists a need for current, valid, and reliable data to support or refute the perspectives underlying this inquiry.…”
Section: Tanner Defining the Physical Environmentmentioning
confidence: 99%
“…Even when concern is expressed for the quality of the design of school facilities, outdoor spaces and other non-classroom spaces are often the least-considered or are perceived only as places of secondary importance with no direct impact on the principal goals of schools (Catling, 2005). Tanner (2000) states that often the design of "green areas, natural quiet areas, and play areas" are not given enough attention. When there is some concern for the design of school grounds it is usually shaped according to adults' vision of what children ought to do during their recess hours (Collins & Coleman, 2008;Dyment & Bell, 2007).…”
Section: School Environment and Childrenmentioning
confidence: 99%
“…When it comes to the design of children's spaces, such as schools, the spaces are often shaped with mediocre design and building standards (Catling, 2005;Collins & Coleman, 2008;Tanner, 2000). Even when concern is expressed for the quality of the design of school facilities, outdoor spaces and other non-classroom spaces are often the least-considered or are perceived only as places of secondary importance with no direct impact on the principal goals of schools (Catling, 2005).…”
Section: School Environment and Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of school design on various aspects of academic achievement have been studied by a number of researchers before. Tanner (2000) found that four design factors to correlate with student learning outcomes in elementary schools in USA: access to technology for teachers, freedom of movement within the school and among learning environments, overall positive impression of the learning environment and positive outdoor spaces that are in harmony with nature. Barrett, Zhang, Moffat and Kobbacy (2013) showed that six design parameters of the built environment: colour, choice, connection, complexity, flexibility and light have demonstrable impact on the learning rates of pupils in primary schools.…”
Section: Introductionmentioning
confidence: 99%